2014
DOI: 10.15605/jafes.029.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Mellitus and Metabolic Syndrome in Prostate Cancer Patients given Androgen Deprivation Therapy

Abstract: Objective. To compare the prevalence of diabetes mellitus (DM) and metabolic syndrome (MetS) in prostate cancer patients with or without androgen deprivation therapy (ADT).Methodology. This is a cross-sectional analytic study of prostate cancer patients from the Integrated Surgical Information System database of the Philippine General Hospital from [2004][2005][2006][2007][2008][2009][2010]. Patients who received either continuous monthly GnRH agonist injection for at least 6 months or underwent bilateral orch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…A new onset fasting hyperglycaemic episode was noted in four (4.10%) patients in the MC group. Studies have confirmed the link of ADT and diabetes mellitus [50][51][52][53][54][55]. There is a decrease in number of skeletal muscles fibres during ADT therapy leading to reduction in peripheral glucose uptake by muscle tissues.…”
Section: Discussionmentioning
confidence: 83%
“…A new onset fasting hyperglycaemic episode was noted in four (4.10%) patients in the MC group. Studies have confirmed the link of ADT and diabetes mellitus [50][51][52][53][54][55]. There is a decrease in number of skeletal muscles fibres during ADT therapy leading to reduction in peripheral glucose uptake by muscle tissues.…”
Section: Discussionmentioning
confidence: 83%